The Influence of Education on Increasing the Knowledge of Mothers of Toddlers About the 8 Functions of the Family - Hawa Cahya Purnama; Indah Budiastutik; Marlenywati Marlenywati; Elly Trisnawati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Mother's knowledge is very important because it is one of the contributing factors to the emergence of stunting in toddlers. Mothers with low knowledge have a higher risk of their children experiencing stunting compared to mothers with sufficient knowledge.The family plays a very important role in efforts to prevent stunting. Preventing stunting in families can be associated with eight family functions that support each other. This study aims to analyze the effect of education on improving the knowledge of mothers with toddlers regarding the 8 family functions. The eight family funtions are the religious function, sosio-cultural function, affection function, protection function, reproduction function, socialization and education function, economic function, and environmental development function. This research method is quantitative, using a quasi-experimental design with a pretest-posttest questionnaire instrument. The sample consists of 30 mothers with toddlers at risk of stunting in the Family Planning Village (Kampung KB), Lembah Murai Village. Data analysis used the Paired T-Test to test the effect of education on the 8 family functions before and after the intervention. The results show an average knowledge score increase of 21.76 after the intervention. The results of the Paired T-Test indicate a p value of 0,000, which signifies a statistically significant difference between the scores before and after the education on the 8 family funtions.Therefore, a good family role is very important in forming healthy living patterns in toddlers, making the active role of the family the key to supporting the optimal growth and development of toddlers. It is recommended that the education program be carried out regularly by involving cadres as active companions to support the understanding of mothers with toddlers in stunting prevention. Keywords: Education, Family Function, Stunting, Knowledge of Mothers of Toddlers